Serum acylcarnitines levels as a potential predictor for gestational diabetes: a systematic review and meta-analysis - Luo, Hairong; Zhu, Zanlei (Frontiers in Public Health, 2023)
Aims Gestational diabetes mellitus (GDM) stands as a prevalent obstetric complication bearing consequential health implications for both mother and child. While existing studies have probed the alterations in acylcarnitines during GDM, an updated systematic meta-analysis is needed to consolidate these findings. Hence, this study endeavours to furnish a comprehensive systematic review and meta-analysis delineating the association between acylcarnitines and GDM, aimed at bolstering diagnostic accuracy and preventive measures against GDM. Methods To extract pertinent studies for this meta-analysis, we meticulously scoured databases such as PubMed, Web of Science, Embase, and Cochrane Library up until May 2023. The inclusion criteria were studies contrasting plasma metabolomics between two cohorts: women diagnosed with GDM and normoglycemic pregnant women. Weighted mean differences (SMDs) and 95% confidence intervals (CIs) were calculated using random-effects models. The I2 index was employed to quantify heterogeneity amongst the studies. All meta-analyses were executed using Stata version 12.0. Results Our meta-analysis included eight studies encompassing 878 pregnant women. The analysis disclosed that relative to normoglycemic pregnant women, women with GDM exhibited significantly elevated levels of Short-Chain Acylcarnitines (SCAC) (SMD: 0.19, 95% CI: 0.02–0.36, I2 = 71.3%). No substantial difference was discerned in fasting total carnitine levels (SMD: 0.15, 95% CI: −0.16–0.31, I2 = 68.2%), medium-chain acylcarnitines (MCAC) (SMD: 0.08, 95% CI: −0.02–0.36, I2 = 79.0%), and long-chain acylcarnitines (LCAC) (SMD: 0.04, 95% CI: −0.06–0.15, I2 = 0%). Neither funnel plot assessment nor Egger’s regression and Begg’s rank correlation tests indicated any evidence of publication bias. Conclusion Our meta-analysis suggests that elevated levels of SCAC may heighten the risk of GDM onset. Given GDM’s deleterious impact on pregnant women and their offspring, these findings underscore the clinical imperative of managing this condition. Early surveillance of plasma metabolomic profiles, particularly serum acylcarnitine concentrations, may equip clinicians with a valuable tool for timely diagnosis and intervention in GDM.